Impact of Early Extubation and Reintubation on the Incidence of Bronchopulmonary Dysplasia in Neonates - Berger, Jessica; Mehta, Paulomi; Bucholz, Emily; Dziura, James; Bhandari, Vineet (American Journal of Perinatology, 2014)
Objective The objective of this study was to assess rates of bronchopulmonary dysplasia (BPD) and BPD/death in infants first extubated between day of life (DOL) 1 to 3 versus 4 to 7, 8 + , and impact of reintubation.Study Design We included infants with gestational age ≤ 28 weeks, birth weight ≤ 1,000 g, and intubation on DOL 1. Proportional hazards regression modeled time to BPD and BPD/death, adjusting for potential confounders.Results Of 262 infants, 101 (38.55%), 41 (15.65%), and 120 (45.80%) were extubated between DOL 1 to 3, 4 to 7, and 8 + , respectively. Extubation between DOL 4 to 7 and DOL 1 to 3 was associated with an increased hazard of developing BPD (hazard ratio [HR], 1.7; 95% confidence interval [CI], 1.0–2.8; p < 0.05). Extubation on DOL 8+ was associated with a significantly increased hazard compared with extubation between DOL 1 to 3 (HR, 16.9; 95% CI, 10.5–27.1; p < 0.0001) and DOL 4 to 7 (HR, 10.0; 95% CI, 6.1–16.3; p < 0.0001). Similar results were noted with BPD/death. Reintubation did not affect BPD and BPD/death.Conclusions Delaying extubation beyond the first 3 and 7 days was associated with an increased risk of BPD and BPD/death. Reintubation did not impact outcomes.
Keywords: neonate; invasive ventilation; NIPPV; BPD